The distribution of blood flow, oxygen consumption, and work output among the respiratory muscles during unobstructed hyperventilation. - Robertson, C H (1977)
An animal model was developed to describe respiratory muscle work output, blood flow, and oxygen consumption during mechanical ventilation, resting spontaneous ventilation, and the increased unobstructed ventilatory efforts induced by CO2 rebreathing. Almost all of the work of breathing was inspiratory work at all ventilatory levels; thus, only blood flows to the diaphragm and external intercostals increased in the transition from mechanical to spontaneous ventilation, and they further increased linearly as ventilatory work was incrementally augmented ninefold by CO2 rebreathing. No other muscles of inspiration manifest increased blood flows. A small amount of expiratory work was measured at high ventilatory volumes during which two expiratory muscles (transverse abdominal and intercostals) had moderate increases in blood flow. Blood pressure did not change, but cardiac output doubled. Arterial-venous oxygen content difference across the diaphragm increased progressively, so oxygen delivery was augmented by both increased blood flow and increased oxygen extraction at all work loads. Oxygen consumption increased linearly as work of breathing increased, so efficiency did not change significantly. The mean efficiency of the respiratory muscles was 15.5%. These results differ significantly from the patterns previously observed by us during increased work of breathing induced by inspiratory resistance, suggesting a different distribution of work load among the various muscles of respiration, a different fractionation of oxygen delivery between blood flow and oxygen extraction, and a higher efficiency when shortening, not tension development, of the muscle is increased.